ANALISIS MINAT REMAJA DALAM MENGGUNAKAN MOBILE BANKING SEBAGAI ALAT TRANSAKSI KEUANGAN - Afrizal, Rifa; Gunawan, Alfaz Syihab; Gunawan, Irfan; Hatimatunnisani, Hani (LPPM Politeknik Pajajaran ICB, 2025)
This study aims to analyze the interest of teenagers in utilizing mobile banking as a means of financial transactions in the digital era. The type of research used is quantitative with a descriptive approach, data obtained through a questionnaire to 84 respondents. The results of the study showed a fairy high interest of teenagers in using mobile banking. Knowledge and understanding of the features used are also quite good. Teenagers' interest in utilizing mobile banking as a means of financial transactions is influenced by a number of factors, such as ease of use, benefits, and trust in system security.